Categorização da estrutura do raciocínio clínico demonstrado por estudantes de fisioterapia, baseada na taxonomia solo - Rabelo, Helenise Aparecida Pereira (2024)
The clinical reasoning (CR) of physiotherapy students must evolve during graduation, being fundamental to the teaching practice to understand the mechanisms involved in this process development. The objective of this study was to categorize the structure of the CR demonstrated by physiotherapy students, according to the assumptions of the SOLO Taxonomy - Structure of Observing Learning Outcome, which allows classifying the level of cognitive complexity demonstrated for a task. This is a cross-sectional, descriptive, observational study with qualiquantitative analysis, which evaluated the diagnostic accuracy and categorized the cognitive complexity demonstrated by physiotherapy students in the 7th period (initial clinical cycle) and 9th period (final clinical cycle) of UNIFENAS/Campus Divinópolis, in the course of solving a physiotherapeutic case, in which the student was instructed to provide the clinical diagnosis (CD) and physiotherapeutic diagnosis (PD), explain the diagnostic criteria, and conduct for the case. The evaluation and categorization of students’ responses was performed by tree physiotherapists with experience in the area, after being guided in relation to the procedures. Results: The study included 38 students, n = 8 (21.1%) of 7th period and n = 30 (78.9%) of 9th period, constituting the total number of enrolled in these periods. The data showed low accuracy for CD in both periods, in whichonly 28.9% of the students provided the correct CD. For the PD, the students demonstrated a high success rate (78.9%), with a frequency in 9th period higher than in 7th period (83.3% vs 62.5%). The justification’ categorization provided by the students showed that most of them demonstrated a level of superficial cognitive complexity in the diagnostic explanation and in the physiotherapeutic conduct. No correlation was found between SOLO category and accuracy of CD or PD. Conclusion: the participants of this study demonstrated good accuracy for providing PD despite the low accuracy for CD, and presented answers with cognitive complexity of superficial learning in the CD explanation and for physiotherapeutic conduct.